2012
DOI: 10.1590/s1677-55382012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Gender reassignment surgery - a 13 year review of surgical outcomes

Abstract: Regarding male to female GRS, a review of the current literature demonstrated scarce description of complications and their treatment options. These findings motivated a review of our surgical outcomes. Results showed a great number of adverse events, although functionality preserved. Comparision of our outcomes with recent publications additionally showed that treatment options provide satisfying results. Moreover, outcomes reaffirm penile inversion vaginoplasty in combination with glans-derived sensate clito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 31 publications
5
84
0
Order By: Relevance
“…Neovaginal stricture was reported in six studies [21,22,26,28,30,31]. Stricture of the neovaginal introitus was present in 84 of 674 studied patients (12%, range 4.2–15%).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Neovaginal stricture was reported in six studies [21,22,26,28,30,31]. Stricture of the neovaginal introitus was present in 84 of 674 studied patients (12%, range 4.2–15%).…”
Section: Resultsmentioning
confidence: 92%
“…[21], who used a urethral flap for the anterior neovaginal wall. Genital pain was present in 9% [28] and 3% [31] in patient groups of, respectively, 232 and 332 MtF patients.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Outcomes research on other transition related interventions, including speech therapy, are scattered throughout the literature [51,52,53]. Studies exist on patient satisfaction with surgical outcomes [54,55], but not on satisfaction with hormonal treatment outcomes separate from overall surveys of access to care or satisfaction with overall health care services in a given setting. Studies eliciting patient identified objective outcomes and priorities are themselves lacking.…”
Section: Research To Datementioning
confidence: 99%